Representation of The Values of Local Wisdom of Sunda Community in Shaping the Profile Pancasila Students in Civics Education - Fadil, Khaidir; Islami, Fidain Fauzanil; Noor Isna Alfaien; Andestend; Ardiyansah, Fahmi (STKIP Al Islam Tunas Bangsa dan HEPI, 2025)
This study explores the representation of Sundanese local wisdom values, particularly silih asih (compassion), silih asah (mutual learning), and silih asuh (mutual care), in shaping the Pancasila Student Profile within Civics Education. Using a qualitative library research approach, the study analyzes relevant literature, cultural texts, and educational policies to identify the integration of these values in fostering civic morality. Findings show that Sundanese local wisdom strongly correlates with the dimensions of religiosity, noble character, mutual cooperation, and global diversity, thereby enriching character education. The incorporation of these values encourages empathy, social awareness, and spiritual consciousness among students, reflecting both cultural heritage and national identity. The study concludes that local wisdom provides a contextual and sustainable foundation for strengthening the implementation of Pancasila values in education. It recommends Civics Education to consistently integrate local traditions to nurture holistic civic engagement